2022
DOI: 10.3390/dj10120230
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a 1-Year COVID-19 Extension on Undergraduate Dentistry in Dundee: Final Year Students’ Perspectives of Their Training in Oral Surgery

Abstract: Background: The detrimental impact of the COVID-19 pandemic on dental education prompted the Scottish Government to fund an additional year to the dental course to ensure that the students had the necessary clinical experience. The aim of the study was to better understand the final year student perceptions of this extension on their oral surgery experience at the University of Dundee. Methods: This mixed methods study consisted of an anonymous online questionnaire and a focus group. Results: Forty-one student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Previous studies have consistently revealed the crucial role of con dence as a trait in physicians, highlighting the unique relationship between post-training con dence and competence [13]. Participants who underwent effective training demonstrated a high level of con dence, which in turn can enhance various motivational elements, including ambition, effort, creativity, and more, during their learning tasks [14]. Our survey shows that participants using the training model tended to acquire higher skill assessment scores (80.741±8.321 vs. 76.817±9.075), although the difference was not statistically signi cant(P=0.167).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have consistently revealed the crucial role of con dence as a trait in physicians, highlighting the unique relationship between post-training con dence and competence [13]. Participants who underwent effective training demonstrated a high level of con dence, which in turn can enhance various motivational elements, including ambition, effort, creativity, and more, during their learning tasks [14]. Our survey shows that participants using the training model tended to acquire higher skill assessment scores (80.741±8.321 vs. 76.817±9.075), although the difference was not statistically signi cant(P=0.167).…”
Section: Discussionmentioning
confidence: 98%
“…Undergraduate dental student experience of surgery across the United Kingdom is quite limited [ 23 , 24 ] and we have shown that at the end of final year students still lack confidence in surgery [ 25 ]. The potential consequences and wider health service cost could be great if poor clinician confidence influences referral patterns with resultant impact on specialist services, patient waiting times and secondary care treatment costs [ 26 ].…”
Section: Discussionmentioning
confidence: 99%